2017
DOI: 10.1371/journal.pntd.0005440
|View full text |Cite
|
Sign up to set email alerts
|

The effect of current Schistosoma mansoni infection on the immunogenicity of a candidate TB vaccine, MVA85A, in BCG-vaccinated adolescents: An open-label trial

Abstract: IntroductionHelminth infection may affect vaccine immunogenicity and efficacy. Adolescents, a target population for tuberculosis booster vaccines, often have a high helminth burden. We investigated effects of Schistosoma mansoni (Sm) on the immunogenicity and safety of MVA85A, a model candidate tuberculosis vaccine, in BCG-vaccinated Ugandan adolescents.MethodsIn this phase II open label trial we enrolled 36 healthy, previously BCG-vaccinated adolescents, 18 with no helminth infection detected, 18 with Sm only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…A stronger Th1 response after the 2 nd vaccination is similar to the lack of bias seen in a study that aimed to investigate the effect of Schistosoma mansoni infection on the TB vaccine, MVA85A candidate vaccine [20]. Investigations involving individuals vaccinated with HPV L1 VLPs have shown strong Th1 and Th2 response in vitro indicated by high levels of IFN-γ, IL-5 and IL-10, especially in individuals with strong antibody titers.…”
Section: Chronic S Mansoni Infection Has No Significant Effect On Cymentioning
confidence: 55%
See 2 more Smart Citations
“…A stronger Th1 response after the 2 nd vaccination is similar to the lack of bias seen in a study that aimed to investigate the effect of Schistosoma mansoni infection on the TB vaccine, MVA85A candidate vaccine [20]. Investigations involving individuals vaccinated with HPV L1 VLPs have shown strong Th1 and Th2 response in vitro indicated by high levels of IFN-γ, IL-5 and IL-10, especially in individuals with strong antibody titers.…”
Section: Chronic S Mansoni Infection Has No Significant Effect On Cymentioning
confidence: 55%
“…Schistosomiasis, has been estimated to affect more than 250 million people with majority of cases occurring in Sub-Saharan Africa [18]. Several studies have shown that parasitic infections, especially schistosomiasis, impair long-term responses of certain vaccines such as BCG [19], TB [20], hepatitis B [21] and tetanus toxoid [22] that require a predominant Th1 response to be effective. During a chronic helminth infection, there is a characteristic induction of a Th2 response which down regulates Th1 responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, SM has no impact on Mtb-specific cytokine production or antibody responses generated by DNA vaccination (33,34); however, it impairs Mtb-specific cytokine production following BCG vaccination and results in higher CFU of both BCG and Mtb (35,36). In humans, SM infection does not impair the generation of Mtb-specific T and B cells by the TB candidate vaccine MVA85A (37). In vitro studies of human PBMCs exposed to SM antigens have demonstrated skewing of Mtb-specific CD4 T cells from a TH1 to a TH2 response; however, human monocyte-derived macrophages exposed to the same antigens have produced contradictory results with one study showing enhanced control and another showing impaired control of Mtb replication in vitro (38,39).…”
Section: Introductionmentioning
confidence: 97%
“…However, as of November 2017, there were ongoing studies looking at aerosolized delivery of the vaccine (NCT01954563; NCT02532036). In 2017, studies were published that addressed the immunogenicity of the candidate tuberculosis vaccine MVA85A in Schistosomiasis‐ infected teenagers (Wajja 2017), and a further efficacy study in HIV‐exposed infants (Nemes 2018). …”
Section: Introductionmentioning
confidence: 99%